Investigation on Effect of Aluminium Hydroxide on Mechanical and Fire Retardant Properties of GFRP- Hybrid Composites. (2017) - Hiremath, Pavan; Arunkumar, H.S.; Shettar, Manjunath
Abstract: There is currently widespread attention in the usage of organic and inorganic filler materials as modifier for polymers due to the significant vary in the performance attainable with very small percentage of additives. The present work is stirred to investigate the effect of aluminium hydroxide on mechanical and fire retardant properties of GFRP- hybrid composites. Three types of composites are fabricated using 0, 3 and 6 wt.% aluminium hydroxide powder with 50 wt.% fibre, remaining matrix material. The composite laminates are fabricated by hand-layup process. Specimens cut and tested according to ASTM standards for mechanical properties and FMVSS standard for fire retardant properties (burning rate).